Affective Strategies to Improve IELTS Speaking Skills In Indonesia: Untapped Strategies to Solve IELTS Speaking Issues in Relation To Gender, Age, and Social Status - Affandi, Akhmad (Eduvelop: Journal of English Education and Development, 2024)
This study aims to find out untapped strategies to solve ielts speaking issues in relation to gender, age, and social status. The increasing importance of English as a global communication tool has led to a surge in demand for IELTS courses in Indonesia. Despite various preparation strategies, many Indonesian IELTS test takers face significant challenges, particularly in the speaking component. This study explores the effectiveness of affective and social strategies in overcoming these challenges, with a specific focus on the impact of gender, age, and social status. Drawing on a combination of literature review and empirical evidence, the study highlights the role of anxiety management, positive self-encouragement, and cultural understanding in enhancing speaking performance. The findings suggest that integrating these strategies into IELTS preparation can lead to improved outcomes for test takers, offering practical recommendations for both learners and educators.